2018
DOI: 10.1002/anie.201802937
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry Imaging with Isomeric Resolution Enabled by Ozone‐Induced Dissociation

Abstract: Mass spectrometry imaging (MSI) enables the spatial distributions of molecules possessing different mass‐to‐charge ratios to be mapped within complex environments revealing regional changes at the molecular level. Even at high mass resolving power, however, these images often reflect the summed distribution of multiple isomeric molecules, each potentially possessing a unique distribution coinciding with distinct biological function(s) and metabolic origin. Herein, this chemical ambiguity is addressed through a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
200
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 168 publications
(237 citation statements)
references
References 37 publications
33
200
2
2
Order By: Relevance
“…sodium acetate has been found to be bene cial for the OzID, as the sodiated lipids have a higher yield of ozonolysis products compared to the protonated or potassiated lipids. 39,57,61) is is consistent among various publications, indicating that sodium has a faster reaction rate and suggesting the participation of the charge carrier, perhaps via chelation of the double bond, in the mechanism of the reaction. 56,58) It has also been found that the trans isomer reacts faster than the cis isomer.…”
Section: Ozone-induced Dissociationsupporting
confidence: 86%
“…sodium acetate has been found to be bene cial for the OzID, as the sodiated lipids have a higher yield of ozonolysis products compared to the protonated or potassiated lipids. 39,57,61) is is consistent among various publications, indicating that sodium has a faster reaction rate and suggesting the participation of the charge carrier, perhaps via chelation of the double bond, in the mechanism of the reaction. 56,58) It has also been found that the trans isomer reacts faster than the cis isomer.…”
Section: Ozone-induced Dissociationsupporting
confidence: 86%
“…Notably, the same pair of sn-isomers was found to distribute distinctly in the tumor region relative to surrounding tissue in a mouse brain section, as recently revealed by OzID MALDI-imaging 31 and DESI-UVPD- imaging. 33,45 Our data clearly suggest that PC 16:0_18:1 may contain four structural isomers from combinations of two snisomers and two C]C location isomers of the C18:1. Quantitative comparison of each individual isomer, however, is challenging for the current workow because C]C isomeric ratios of the sn-2 fatty acyl chain cannot be measured independently.…”
Section: Analysis Of Isomeric Pcs From Human Breast Cancerous Tissuementioning
confidence: 61%
“…Several recent MS imaging studies clearly demonstrated that lipid isomers, including fatty acyl compositional isomers, sn-, and C]C location isomers, were distributed heterogeneously in tissue sections or among different types of tissues, likely carrying distinct functions. [31][32][33]45 In an earlier study, we reported that changes of C]C location isomers were more sensitive to pathological conditions than lipid prole changes. 19 In this study, we were interested to test if changes of PC snisomers would differentiate lipidomes of diseased and healthy states, which may be potentially used as markers in biomedical and clinical studies.…”
Section: Analysis Of Isomeric Pcs From Human Breast Cancerous Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…Isomer‐resolved MALDI‐MSI has also been reported using OzID . This work provided the first example of the differentiation of both db‐ and sn ‐isomers during MSI.…”
Section: Ms Imaging With Isomer Resolutionmentioning
confidence: 99%